Re-Visiting Translation of the Yemeni Constitution in the Light of House’s Revised Model - Al-Mizgagi, Essam Hassan Naji (Thamar University, Yemen, 2025)
Translator is always between the two horns of the dilemma: he needs to make balance between preserving accuracy of meaning, function and style of Source Language (SL) and maintaining acceptability of the translated text with all its potentials in the Target Language (TL) which, sometimes, makes translation so difficult, if not impossible. This study investigated the quality of the translation of the constitution of the Republic of Yemen through House’s revised model (2015). This model was found within Hallidayan components of discourse and functions that received acceptability and was used as one of the most common qualitative tools of Translation Quality Assessment (TQM). The model depends on a three-layer scheme of analysis: lexical, syntactic, and textual. Then, based on the previous analysis, the study compared these discursive components in the target text (English version) to their equivalent in the source text (Arabic version). The study concluded that the translator, partially, succeeded in transferring the potential meaning from Arabic into the English, whereas he, in some other parts of the target text, fell short to render the source text satisfactorily based on House’s model (2015) which was appropriate for providing a qualitative account for the translation of the constitution of the Republic of Yemen.
Keywords: Legal translation; Yemeni constitution; Translation Quality; House’s Model; Translation assessment